Play It Again: Partner Choice, Reputation Building and Learning From Finitely repeated Dilemma Games. (25th July 2016) - Kamei, Kenju; Putterman, Louis
Abstract : Often the fuller the reputational record people's actions generate, the greater their incentive to earn a reputation for cooperation. However, inability to 'wipe clean' one's past record might trap some agents who initially underappreciate reputation's value in a cycle of bad behaviour, whereas a clean slate could have been followed by their 'reforming' themselves. In a laboratory experiment, we investigate what subjects learn from playing a finitely repeated dilemma game with endogenous, symmetric partner choice. We find that with a high cooperation premium and good information, investment in cooperative reputation grows following exogenous restarts, although earlier end‐game behaviour is observed.